1963
DOI: 10.1243/pime_proc_1963_177_052_02
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Plastic Deformation in Rolling Contact

Abstract: When two metal cylinders roll together under a contact pressure sufficient to cause yielding, a surprising mode of plastic deformation occurs. The surface of each cylinder is progressively displaced in the forward direction of rotation relative to the core by plastic shearing in a thin subsurface layer. This phenomenon was first observed by Crook (6) in 1957 and the results of a more complete experimental investigation are reported by Hamilton (9) in an accompanying paper. In this paper an attempt is made to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(49 citation statements)
references
References 5 publications
0
49
0
Order By: Relevance
“…Peak pressures of the order of 1 GPa or higher are currently encountered, so that not only the elastic limit is passed, but actually also the elastic shakedown and plastic shakedown. Classical experiments on twin-disk rigs such as Crook [1], Merwin [2] (see also [6]), and Hamilton [7], typically used "soft" materials such as copper. This choice was probably suggested to amplify (and therefore make more easily measurements) plastic deformations, but at the same time copper has a quite marked cyclic hardening behaviour and the mechanism of ratchetting in this material is very different from that of rail steel, ultimately more important for railway industry.…”
Section: Introductionmentioning
confidence: 99%
“…Peak pressures of the order of 1 GPa or higher are currently encountered, so that not only the elastic limit is passed, but actually also the elastic shakedown and plastic shakedown. Classical experiments on twin-disk rigs such as Crook [1], Merwin [2] (see also [6]), and Hamilton [7], typically used "soft" materials such as copper. This choice was probably suggested to amplify (and therefore make more easily measurements) plastic deformations, but at the same time copper has a quite marked cyclic hardening behaviour and the mechanism of ratchetting in this material is very different from that of rail steel, ultimately more important for railway industry.…”
Section: Introductionmentioning
confidence: 99%
“…Examining the nature of the damage during cyclic contact displacement, Madlin [22][23] has shown that under contact pressure, the shear stress required to overcome the static frictional resistance will have a maximum at the center of the circular contact area. While Madlin's analysis assumes elastic conditions, the three-dimensional nature of the problem and local plasticity effects have been considered recently using numerical techniques [24][25][26][27][28]. There are three conditions -stick, partial slip and general slip [29][30][31][32].…”
Section: Local Fatigue Damagementioning
confidence: 99%
“…The approach is to first determine the elastic stresses in the half space, use these as the initial conditions for determining the plastic stresses, then elastically unload the material to determine the residual stress state. This procedure was first used by Menvin and Johnson [9] to analyze stresses induced by rolling contacts and is provided in flow chart form by Suh [lo].…”
Section: Elastic-plastic Plowing Modelmentioning
confidence: 99%